SPECIFICS OF SATISAFACTION WITH LIFE AND OF MOTIVATION AMONG STUDENTS ENGAGED IN CREATIVE WORK - Akhryamkina, T. A. (Modern Psychology, 2019)
The article dwells on the problems of professional and personal self-identification of young people and analyzes characteristic specifics of motivation towards learning and of satisfaction with life among students involved in a creative collective. The article summarizes the approaches towards the notion of “satisfaction with life” among psychologists representing various standpoints. Based on the research the role of creative work done by students is identified with respect to their future professional establishment.
Keywords: self-identification, motivation towards learning, satisfaction with life, creativity